Profiling Bioactive Compounds and Key Nutrients in Pacific Island Crops and Marine Resources - Singh, Sunil (Technical Centre for Agricultural and Rural Cooperation, 2019)
This report gives insights into the current status of knowledge on composition of key nutrients and bioactive compounds, known or associated with traditional crops and seafood consumed in seven Pacific Island countries, namely Fiji, Kiribati, Marshall Islands, Samoa, Solomon Islands, Tonga, and Vanuatu. Information was initially gathered through guided interviews with traditional knowledge experts. Based on their responses and a systematic literature review of 433 scientific articles, a total of 75 crops and marine resources were identified as commonly consumed and/or having health and nutrition benefits or foods which could be better used in the daily diets. Traditional leaders also gave reasons for declining consumption and limited utilisation of traditional foods. These included loss of traditional varieties, e.g. breadfruit and yam; loss of traditional knowledge on edible plants and seaweed from the wild, and lack of awareness on nutritional value and health benefits.